PERAN KOMITMEN DALAM PEMASARAN RELASIONAL UNTUK KONTEKS HUBUNGAN B2C - Tanti Handriana (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2015)
The purpose of this study was to analyze the application of the concept of relationship marketing at nonlaba organization, namely philanthropic management organization, with a focus on the role of the construct of relational commitment as a mediator variable. The research also aims to analyze the influence of variables nonmaterial benefits, geographical proximity and social proximity to the relational commitment, as well as to analyze the effect of relational commitment on cooperation with the managing organization philanthropic donors. The study was conducted on 412 donors. The results of questionnaires processed by SEM analysis techniques using software AMOS 4. Of the four hypotheses proposed in this study, as many as three hypotheses supported, namely H1, H3, and H4. Meanwhile, for the H2 is not supported. Thus, the findings of this study support the social exchange theory (Thibaut and Kelley, 1959; Blau, 1964; Homans, 1968), and supports kosep relationship marketing (Morgan and Hunt, 1994). The concept of variable mendudukan relational trust and commitment as the variable a central role in the relationship between individuals and organizations. The holistic conclusions of this study that this research model empirically supported for the second criterion variables can be explained by variables antesendennyaKeywords: relational marketing, relational commitment, nonmaterial benefits, non-profit organizations